The Influence of Leadership Style, Workload, Compensation and Organizational Culture on Performance of Auditors in National Private Company - Muthi’atul Khasanah; Olfin Ishak; Walla Astianty Putri; Bella Suci Novitri; Nurdin Yusuf (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
Using organizational culture as a moderator, this study seeks to gather empirical data on the effects of pay, workload, and leadership style on auditor performance. This investigation focused on certified auditors. Purposive sampling is used in the process for sample determination. Auditors were given questionnaires to complete, and 100 questionnaires may be processed to create the sample for this study. With the aid of IBM SPSS, multiple linear regression analysis (MLRA) and moderated regression analysis (MRA) are the data analysis techniques used. The study's findings indicate that the performance of an auditor is influenced by workload more so than by the auditor's remuneration or leadership style. Organizational culture, therefore, has limited control over the workload and compensation of auditors. It can, however, attenuate the impact of leadership style on auditor performance.